Spatial Analysis of the Vegetation Condition Index of Al-Hamdania District by Remote Sensing Dataset - Ali, Sabah Hussein; Thannoun, Rayan Ghazi; Adeeb, Hadeer Gh. M. (Iraqi Journal of Science, 2026)
Drought is a natural hazard that occurs as a result of decreased rainfall and water storage. It has a significant impact on the agriculture sector. In this paper,  monitoring the drought in the Al-Hamdaiya district located east of Mosul city in the Nineveh Governorate, Northern Iraq, was performed for years 2017, 2018, 2019, 2022, and 2024 by integrating remotely sensed data and geographic information systems (GIS). Spatial and temporal distribution changes of the drought phenomenon for the study area were verified by Normalized Difference Vegetation Index (NDVI) and Vegetation Condition Index (VCI) using Landsat 8 (Operational Land Imager: OLI) images during April month. The results indicated that the study area experienced relatively no drought between 2019 and 2024. However, there was a significant increase in drought conditions during 2017, 2018, and 2022. The percentage of drought-free areas fluctuated between 11.73-91.58% from 2017-2024. Among the drought categories, extreme and moderate drought accounted for the largest percentages, followed by severe and mild drought.